The Controversy of Parental Roles in Supporting Children’s Education in the Digital Era - Mohammad Jefri Nabili Nur Faizin; Imron Fauzi (Linguanusa : Social Humanities, Education and Linguistic, 2025)
Introduction the Problem: This study explores the controversy surrounding parental roles in supporting children’s education in the digital era. Purpose: The research investigates how parents adapt to the shift from conventional parenting to digital-based learning assistance. Method: Using a qualitative descriptive approach, data were gathered through interviews, observations, and documentation involving parents, teachers, and students. Findings: The findings show a clear transformation in parenting practices, with parents increasingly using digital tools and online platforms to guide children’s learning. This involvement positions parents as both supervisors and collaborators in digital learning environments. However, the study also identifies a social tension: while some parents believe digital supervision ensures focus and safety, others worry that excessive control may limit children’s autonomy and self-regulation. The results emphasize that balanced digital mediation supported by adequate digital literacy enhances children’s motivation, discipline, and engagement in online learning. Stronger collaboration between schools and families further improves the effectiveness of learning support. Limitations and Recommendations: In conclusion, digital parenting requires a balance between guidance and autonomy. The study provides theoretical insight into evolving digital parenting practices and offers practical implications for strengthening parental digital literacy and school–family partnerships.